PI3K/Akt/mTOR pathway participates in neuroprotection by dexmedetomidine inhibits neuronic autophagy following traumatic brain injury in rats - Zhang, Man-He; Zhou, Xiu-Min; Gao, Jun-Ling; Wang, Kai-Jie; Cui, Jian-Zhong (International Journal of Research in Medical Sciences, 2017)
Dexmedetomidine (Dex) has been demonstrated to provide neuroprotective effect against brain injury in the central nervous system. However, the underlying mechanism of this neuroprotection remains unclear. In this study, we explored whether Dex has the protective potential in rat models of traumatic brain injury(TBI). More importantly, our study further investigated the role of neuronic autophagy induced by PI3K/Akt/mTOR pathway in this neuroprotective action. Adult male Sprague-Dawley rats were subjected to a diffuse cortical impact injury caused by a modified weight-drop device and Dex (15ug/kg, i.v.) was administered immediately after TBI. Wet-dry weight method was used to evaluate brain edema. Motor function outcome was assessed by Neurologic Severity Score and the spatial learning ability was evaluated in a Morris water maze. The co-localization of microtubule-associated protein 1 light chain 3(LC3) and neuronal nuclei (NeuN), or LC3 and mammalian target of rapamycin (mTOR) were analyzed by immunofluorescence respectively. The expression of LC3, Phosphorylated protein kinase B (p-Akt) and p-mTOR were quantified using Western blot analysis. Our results showed treatment of rats exposed to TBI with Dex caused not only marked reduction in cerebral edema, motor and cognitive functions deficits, but also a decrease in LC3 levels and a increase in p-Akt and p-mTOR levels. Taken together, these findings indicated that treatment with Dex after TBI could inhibited neuronic autophagy in the hippocampus mediated by the activation of the PI3K/Akt/mTOR pathway, finally promoting neurological recovery. Abbreviations: TBI, Traumatic brain injury; Dex, Dexmedetomidine; LC3, Light chain 3; NeuN, Neuronal nuclei; mTOR, Mammalian target of rapamycin; Akt, Protein kinase B